'n Toekoms vir die chronies geestesversteurde - M. Coetsee (AOSIS, 1983)
The Lodge programme was started at the Austin State Hospital a few years ago to train chronically mentally ill patients, who would otherwise have spent the rest of their lives in hospital, to become independent members of the community. It is an intensive training program for which patients are carefully selected. Significant aspects are that the patients function as members of a problem-solving group and are taught cleaning skills with which they earn an income. There are five levels of progress in the first phase, on completion of which the group graduates from the programme. In the second phase the group moves into a house in the community and continues with cleaning contracts for at least a year before individual members may withdraw.